Managing global business environment with tawhidic paradigm for the betterment of Muslim ummah - Benjasom, Husnee; Sarif, Suhaimi Mhd (2012)
This paper explores the influence of Tawhidic paradigm in the mindset of managers in managing business environment with global perspectives to sustain competitiveness and betterment of the Muslim Ummah. Tawhidic paradigm embraces global perspective from Oneness of God perspective that emphasizes on the sole submission, obedience and compliance to the Will of God. Managing global business environment is about how managers use their understanding of global perspective to work with and through people to achieve organizational goals with efficiency and effectiveness. The integration of Tawhidic paradigm into the management of global business environment enables businesses to create and sustain unique capacity to take advantage of the opportunities within the Tawhidic values. The study conducted personal interview with 10 student of Graduate School of Management International Islamic University Malaysia to explore the influence of Tawhidic paradigm on the global perspective of managers in managing global business environment for betterment of Muslim Ummah. The results of the study show that the Tawhidic paradigm is acceptable as universal paradigm for the world community due to its emphasis on the betterment of Muslim Ummah, which by default includes all races of humanity. The operationalization of Tawhidic paradigm into managerial skill and thinking should enable managers face global business challenges such as various regional trade alliances, different structures of global business organizations, and the global political/legal/economic environment. The theoretical implication for the study is on the integration of conventional managerial paradigm with Tawhidic paradigm. As for the practical implication for the study is the operationalization of Tawhidic paradigm into standard operating procedure. However, the results of the study are not conclusive and cannot be generalized. The study proposes future studies to use case studies method and to include key business stakeholders into the focus group discussion.